Proceedings of the 1st Annual Conference on Education and Social Sciences (ACCESS 2019) 2020
DOI: 10.2991/assehr.k.200827.006
|View full text |Cite
|
Sign up to set email alerts
|

“I Feel Nervous and Lose My Ideas When Having Presentation”: Mapping Senior Students’ Challenges in Academic Oral Presentation in English

Abstract: This study explored senior students' challenges when presenting their research proposal and thesis in English. This study was conducted in the English Teacher Education Department of the University of Nahdlatul Wathan Mataram. Five students who did their final project and five lecturers who were involved in reviewing activities were investigated in this study. The results of this study were expected to better understand students' major problems, sources of problems and how these could be tackled. A qualitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Previous studies reported that psychological issues during speaking performance were reported to be among the biggest issues (Said & Weda, 2018) which cause the EFL students unable to carry themselves well (i.e. Choi et al, 2019, Arifin, 2017, Hue, 2010, Hadi, et, al, 2020. To overcome psychological challenges, some previous studies suggest the teachers to do intervention to help the students out of their anxiety (Ayuningtyas, 2020).…”
Section: Figure 314 Developing the Academic Skillsmentioning
confidence: 99%
“…Previous studies reported that psychological issues during speaking performance were reported to be among the biggest issues (Said & Weda, 2018) which cause the EFL students unable to carry themselves well (i.e. Choi et al, 2019, Arifin, 2017, Hue, 2010, Hadi, et, al, 2020. To overcome psychological challenges, some previous studies suggest the teachers to do intervention to help the students out of their anxiety (Ayuningtyas, 2020).…”
Section: Figure 314 Developing the Academic Skillsmentioning
confidence: 99%
“…Academic oral presentation (AOP) is an important oral genre for students at the tertiary level. When academic oral presentations (AOPs) are evaluated and graded, the task is challenging (Hadi et al, 2019) and there is anxiety (Kho andTing, 2021, Grieve et al, 2021). Students are afraid of getting evaluated by examiners and have trouble remembering their points which causes anxiety too (Shahar and Abdul Raof, 2021).…”
Section: Introductionmentioning
confidence: 99%